Impact of high-intensity interval training and sprint interval training on peripheral markers of glycemic control in metabolic syndrome and type 2 diabetes - Jiménez Maldonado, Alberto (2020)
Glycemic control is essential to reduce the risk of complications associated with metabolic syndrome (MetS) and type 2 diabetes (T2D). Aerobic and resistance exercise performed alone or in combination improve glycemic control in both conditions. However, perceived lack of time and commitment are considered principal barriers to performing exercise regularly. High intensity interval training (HIIT) and sprint interval training (SIT) can be performed in a fraction of the time required for continuous aerobic exercise. A substantial scientific evidence indicates that HIIT/SIT improve glycemic control to a similar or greater extent than aerobic exercise in populations without MetS or T2D. Likewise, growing evidence suggest that HIIT/SIT improve the glycemic control during MetS and T2D. The aim of this review is to discuss the effects of interval training protocols on peripheral markers of glucose metabolism in patients with MetS and T2D.